(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Open angle glaucoma is characterized by specific lesions of the optic disc and is accompanied by visual field loss in the presence of elevated intraocular pressure (IOP). The management of glaucoma is challenging, the disease has become a matter of rising social and economic concern and a major cause of the deterioration in quality of life in patients [1, 2]. It is important that glaucoma is highly prevalent among economically-active working-age individuals and is the most common cause of certified visual disability [3, 4]. Glaucoma incidence increases with age. Primary open angle glaucoma (POAG) is more common in individuals older than 40 years of age.